Programa cheque-cidadão: avaliação e responsabilidade social do Tribunal de Contas do Estado do Rio de Janeiro - Silva, Aristóteles Lemos da (2008)
In the last decade, many basic transfer income programs have been implemented in Brazil, but the poverty levels have not decreased at the same rate as the resources invested in those programs. Lack of coordination among government, financial supporters, managers and executors of public policies are the major problems. The program 'cheque cidadão', due to the huge volume of resources spent and the participation of religious institutions in the selection and distribution of its benefits, was under an audit process, in September 2004, by the 'Tribunal de Contas do Estado do Rio de Janeiro' (TCE-RJ) government agency. The program was also object of an evaluation research by the 'Instituto de Estudo do Trabalho e Sociedade' (IETS), in May 2002, with the intention of to understand the managerial process and its impacts (effectiveness) on the focus population. The purpose of this study is to contextualize these two events in the paradigm of the New Public Management (NPM) with standards of efficiency, affectivity and effectiveness and equity, expecting to insert the TCERJ in the field of performance auditing - accountability of results – and favoring the evaluation of public policies performance as a form of contribution to correspond to the growing social demand for a government oriented toward results.